2022
DOI: 10.1039/d1cp04528h
|View full text |Cite
|
Sign up to set email alerts
|

Ultrafast and efficient energy transfer in a one- and two-photon sensitized rhodamine-BODIPY dyad: a perspective for broadly absorbing photocages

Abstract: In view of the demand for photoactivatable probes that operate in the visible (VIS) to near infrared (NIR) region of the spectrum, we designed a bichromophoric system based on a...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
6

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 49 publications
0
9
0
6
Order By: Relevance
“…The synthesis of the fluorophore‐photocage dyads is shown in Scheme 1. Rhodamine 101 was chosen as donor fluorophore since high two‐photon action cross‐sections (σ 2P Φ F ) of 80–110 GM between 810 and 870 nm have previously been determined via TPEF measurements [26] . The bromo‐substituted rhodamine scaffold 6 was synthesized according to literature [31] .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The synthesis of the fluorophore‐photocage dyads is shown in Scheme 1. Rhodamine 101 was chosen as donor fluorophore since high two‐photon action cross‐sections (σ 2P Φ F ) of 80–110 GM between 810 and 870 nm have previously been determined via TPEF measurements [26] . The bromo‐substituted rhodamine scaffold 6 was synthesized according to literature [31] .…”
Section: Resultsmentioning
confidence: 99%
“…In our previous work, we presented a molecular dyad consisting of a rhodamine as two-photon donor fluorophore and a styryl-substituted red-absorbing BODIPY as acceptor photocage. [26] Two-photon excited fluorescence (TPEF) measurements indicated excellent 2PA properties of the used rhodamine derivative. A fast and efficient excitation energy transfer (EET) from rhodamine to BODIPY was confirmed by ultrafast transient absorption measurements and quantum dynamical calculations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…FRET between the antenna and MNI facilitated photolysis to release bis-Fmoc-protected glutamate. Recently, Heckel, Burghardt, and Wachtveitl et al reported a rhodamine-BODIPY dyad (RHO-BPY-PNA) for 2PE-sensitized photodecaging of a carbamate . These systems have potential for use in neurophysiology, yet no examples have been reported to date.…”
Section: Introductionmentioning
confidence: 99%
“…This also led to the search of two-photon activatable PPGs which are meant to address this issue. [151,[163][164][165][166] 2. Coumarin and its derivatives are among the most commonly used photochemically active molecules.…”
Section: Photolabile Protecting Groupsmentioning
confidence: 99%